Monitoring CO2 and SO2 Exhaust Gas Emissions on Tanker Ships With An IoT Based PLC Controller - Nur Fajar, Iqbal; Prayogi, Soni (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2024)
This work discusses the development of a CO2 and SO2 exhaust emissions monitoring system on tankers using a PLC controller connected to the Internet of Things (IoT). The method for measuring gas emissions is carried out in real-time and is integrated with a control system that can optimize ship engine performance to reduce emissions that are detrimental to the environment. This study evaluates the effectiveness of the system in reducing emissions of these harmful gases by taking into account environmental and technical factors. Experimental results show that the use of an IoT-based PLC controller can increase the efficiency of monitoring and controlling gas emissions on tankers, with the potential to be widely applied in the shipping industry. This research contributes to the development of environmentally friendly and sustainable technology in the maritime transportation sector.